What is the best method for assessing lower limb force-velocity relationship? - Giroux, C.; Rabita, G.; Chollet, D.; Guilhem, G. (International Journal of Sports Medicine, 2015)
This study determined the concurrent validity and reliability of force, velocity and power measurements provided by accelerometry, linear position transducer and Samozino`s methods, during loaded squat jumps. 17 subjects performed squat jumps on 2 separate occasions in 7 loading conditions (0-60% of the maximal concentric load). Force, velocity and power patterns were averaged over the push-off phase using accelerometry, linear position transducer and a method based on key positions measurements during squat jump, and compared to force plate measurements. Concurrent validity analyses indicated very good agreement with the reference method (CV=6.4-14.5%). Force, velocity and power patterns comparison confirmed the agreement with slight differences for high-velocity movements. The validity of measurements was equivalent for all tested methods (r=0.87-0.98). Bland-Altman plots showed a lower agreement for velocity and power compared to force. Mean force, velocity and power were reliable for all methods (ICC=0.84-0.99), especially for Samozino`s method (CV=2.7-8.6%). Our findings showed that present methods are valid and reliable in different loading conditions and permit between-session comparisons and characterization of training-induced effects. While linear position transducer and accelerometer allow for examining the whole time-course of kinetic patterns, Samozino`s method benefits from a better reliability and ease of processing.